Mencetak Karakter Calon Guru melalui Active Learning pada Perkuliahan Materi Pembelajaran IPA - Panji Hidayat (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
Prospective teachers have to be educated by means of technical with manage learning to be the best. Knowledge is very required, but prospective teachers must be leant the character and personality. Character is integrated with the curriculum being taught. Teachers are in the lead actor and director of learning. The role of teachers is vital in learning. Prospective teachers must be set from the beginning, start learning content, and output as a blueprint. Learning Materials of Natural Sciences Elementary School isthat must be taken student Elementary School Teacher at the University of Ahmad Dahlan Yogyakarta. Course expected characters teachers can be competent, and ready to be placed anywhere. Any difficult situation in teaching always antusiasm to changeable. Not only ready, but also the professionalism in this profession teachers who have a mandate to educate the children of the nation. Active learning methods applied in The elementary school science teaching expected to improve the character of the ideal candidate in elementary school teacher who is always sensitive, active, responsive, and interactive with the changing times.